Nanoscale to microscale reversal in room-temperature plasticity in SrTiO3 by tuning defect concentration. (November 2020) - Fang, Xufei; Ding, Kuan; Janocha, Stephan; Minnert, Christian; Rheinheimer, Wolfgang; Frömling, Till; Durst, Karsten; Nakamura, Atsutomo; Rödel, Jürgen
Abstract: Incipient room-temperature plastic deformation in single-crystal SrTiO3 at the nanoscale and the microscale is contrasted by applying a scale-dependent indentation technique. Using nanoindentation pop-in, nanoindentation creep, and an evaluation of dislocation spacing via etch pit study, we demonstrate a reversal of yield stress for crystals with different vacancy concentrations and pre-existing dislocation densities. A competing mechanism between dislocation nucleation and dislocation motion on crystal plasticity at different length scales is highlighted. This finding enables us to complete the understanding of dislocation-mediated plasticity for ceramic oxides at the nanoscale as compared to the microscale and macroscale. Graphical abstract: Image, graphical abstract